Live Performance, Carcass, and Bone Quality Responses of Grower and Finisher Broilers to Dietary Metabolizable Energy Levels - Gopinger,E (2017)
ABSTRACT Broiler energy nutrition has attracted attention due to its economic importance, particularly during the rearing period of 22-42 days of age. There are many evidences that broilers changed their feed intake capacity due to genetic selection, especially when good quality pellets are fed, which suggests that modern broiler strains may achieve good performance when fed low metabolizable energy levels. The objective was to evaluate the energy efficiency, performance parameters, bone parameters, and carcass yield of 22- to 42-d-old broilers fed diets with energy levels below or above their requirements, while maintaining the density of all other nutrients. In total, 900 male broilers were distributed in a randomized block design, with five treatments consisting of five ME levels (2850, 2950, 3050, 3150 and 3250 kcal/kg). As expected, increasing dietary metabolizable energy reduced feed intake, feed conversion ratio, and energy efficiency. Interestingly, body weight, carcass and cut yields, and bone quality were not affected (p>0.05) by dietary ME levels. In conclusion, 22- to 42-d-old broilers fed pelleted and crumbled diets containing 2,850 to 3,250 kcal ME/kg (14% difference) achieved the same body weight and carcass yield at slaughter. The results show that energy efficiency may provide a more accurate interpretation of broiler performance than feed conversion ratio, and that broilers are able to change their feed intake, indicating an opportunity to improve their nutritional management.